Haplotype-Based case-control study of the STRK1 region on 5q12 in cerebral infarction - Asai, Satoshi; Sato, Naoyuki; Soma, Masayoshi; Nakayama, Tomohiro (Japanese Journal of Stroke, 2006)
Background—deCODE genetics, Inc. identified a candidate locus (STRK1) for cerebral infarction with a significant LOD score at 5q12 in Caucasians in 2002, and subsequently identified the PDE4D gene as a susceptibility gene at this locus in 2003. The aims of this haplotype-based case-control study were to confirm, using microsatellite markers and single nucleotide polymorphisms (SNPs), whether PDE4D is also a susceptibility gene for cerebral infarction. Methods—Cerebral infarction was defined as non-cardiogenic ischemic stroke with signs and symptoms lasting longer than one month in duration. We genotyped 208 Japanese cerebral infarction patients and 270 non-cerebral infarction controls for 31 SNPs, three dinucleotide microsatellites, and one tetranucleotide vari-able number tandem repeat. Haplotypes were constructed and their frequencies compared between the cere-bral infarction patients and the controls. Results—Seven haplotype blocks were found in the STRKI locus by the linkage disequilibrium analysis. The haplotype-based case-control study revealed that, in addition to the region of the PDE4D gene (p = 0.002), another region (p<0.001) also existed within the STRK1 locus. Conclusions—Our results suggest that there may be a susceptibility region other than that of the PDE4D gene within the locus in Japanese subjects.